Antagonism or Synergism: Role of Tyrosine Phosphatases SHP-1 and SHP-2 in Growth Factor Signaling - Wang, Ning (2006)
SHP-1 and SHP-2 are two SH2 domain-containing tyrosine phosphatases with major pathological implications in cell growth regulating signaling. They share significant overall sequence identity, but their biological functions are often opposite. SHP-1 is generally considered as a negative signal transducer while SHP-2 as a positive one. However, the precise role of each enzyme in shared signaling pathways is not well defined. In this study, we investigated the interaction of these two enzymes in a single cell system by knocking down their expressions with siRNAs and analyzing the effects on epidermal growth factor signaling. Interestingly, knockdown of either SHP-1 or SHP-2 caused significant reduction in the activation of ERK1/2 but not Akt. Furthermore, SHP-1, SHP-2, and Gab1 formed a signaling complex, and SHP-1 and SHP-2 interact with each other. The interaction of SHP-1 with Gab1 is mediated by SHP-2 since it was abrogated by knockdown of SHP-2 and SHP-2, but not SHP-1, binds directly to tyrosine phosphorylated Gab1. Together, the data revealed that both SHP-1 and SHP-2 have a positive role in epidermal growth factor-induced ERK1/2 activation and that they act cooperatively rather than antagonistically. The interaction of SHP-1 and SHP-2 may be responsible for hitherto unexpected novel regulatory mechanism of cell signaling by tyrosine phosphatases.